Problem współliniowości zmiennych w ekonometrii - Zeliaś, Aleksander (Wydział Prawa i Administracji UAM, 1988)
The article offers a critical discussion of the moist important Polish and foreign trends in research into the collineariti of variables. The diversity of approaches signifies that so far the theory of econometrics has not been able to work out a uniform way of acting in conditions of collineariti. It is equally impossible at a present stage to propose a single procedure of eliminating the collineariti as the best procedure. Thus the problem of collineariti remains unsolved. The author believes that collineariti is one of the causes of the emerging crisis in econometric research. He also indicates that the problem of collineariti is unsolvable on a formal plane. The only platform for considering collineariti is the substantial approach.
The problem of collineation of variables in econometrics